Inter-satellite link connection strategy for large-scale low earth orbit satellite networks - YAN Feng; NIE Haojian; XIA Weiwei; SHEN Lianfeng (Tongxin xuebao)
For large-scale low earth orbit (LEO) satellite networks, two new inter-satellite link (ISL) connection strategies named Grid-V and Grid+ were proposed, which improved the traditional Grid connection strategy. The proposed strategies made full use of the ISL connected to adjacent and cross-adjacent orbits. The Grid-V connection strategy abandoned the intra-orbit links of the Grid connection strategy and used ISL of the adjacent and cross-adjacent orbits to form the network topology. The Grid+ connection strategy, while retaining the Grid connection strategy, allowed satellites to establish cross-satellite connections with satellites in the same orbit or the cross-adjacent orbits. For the large-scale LEO satellite network with a Walker-Delta constellation configuration, a shortest distance inter-satellite routing algorithm was designed based on the proposed ISL connection strategies, and system-level simulations were conducted from the perspectives of geometric topology and packet respectively to evaluate the performance of each connection strategy. Simulation results show that, from the perspective of geometric topology, the proposed strategies can effectively reduce the average number of routing hops and path switches. At the packet level, the proposed strategies exhibit better performance in terms of round-trip time and jitter, path occupation ratio, average throughput and so on.